Crystal structure and X-ray absorption spectroscopy of trimethylarsine oxide dihydrate, (CH3)3AsO⋅2H2O. Issue 3 (September 2020) - Reid, Joel W.; Kaduk, James A.; Blanchard, Peter E. R.
Abstract : The crystal structure of trimethylarsine oxide dihydrate, (CH3 )3 AsO⋅2H2 O, (TMAO dihydrate) has been solved using parallel tempering with the FOX software package and refined using synchrotron powder diffraction data obtained from beamline 08B1-1 at the Canadian Light Source. Rietveld refinement, performed with the software package GSASII, yielded orthorhombic lattice parameters of a = 13.3937(4) Å, b = 9.53025(30) Å, and c = 11.5951(3) Å ( Z = 8, space group Pbca ). The Rietveld refined structure was compared with density functional theory calculations performed with VASP and shows reasonable agreement. Arsenic K-edge X-ray absorption spectroscopy analysis also revealed additional information on the electronic structure of the arsenic atom within the TMAO dihydrate structure.